Rhodium and platinum hydrosilylation catalysts for increasing UV stability of poly(dimethylsiloxane) in geostationary environment. (August 2017) - Planes, M.; Le Coz, C.; Lewandowski, S.; Remaury, S.; Solé, S.; Rejsek-Riba, V.; Soum, A.; Carlotti, S.
Abstract: Poly(dimethylsiloxane) (PDMS) resins are widely used for aerospace applications due to their unique properties, such as a high flexibility, good thermal stability and optical transparency in the visible-near-infrared spectral region. Generally, PDMS networks are obtained by hydrosilylation with highly active platinum catalysts (Pt (0) Karstedt). The exposure of such PDMS resins to strong UV irradiations leads to the formation of colloïdal platinum species, and consequently to a loss of optical transparency. Various organometallic derivatives such as chloro (1, 5-cyclooctadiene) rhodium (I) dimer (Rh 1), chloronorbornadiene rhodium (I) dimer (Rh 2), and dichloro (1, 5-cyclooctadiene) platinum (II) (Pt 2) were studied as alternative catalysts for the cross-linking of PDMS. These catalytic systems show high cross-linking efficiencies leading to transparent PDMS resins with small size colloids formation as compared to the Karstedt system. The properties of cross-linked PDMS resins before and after UV irradiations were investigated by dynamic mechanical analysis, thermogravimetric analysis, differential scanning calorimetry, and Vis-NIR spectroscopy. The thermal stability of cross-linked PDMS by all new catalytic systems was increased from 405 °C to 480 °C. After UV irradiations under geostationary conditions, an improved UV stability (up to 12.2%) was observed for the wavelength range 250–400 nm with the Pt 2 catalyst.